The Concept of Nationhood and the Implementation of Hadith on Nationalism in the Salafi Perspective: A Critical Study of Contemporary Islamic Law - Suwarjin; Iim Fahimah; M. Aziz Zakiruddin; Bariah Safrut (Faculty of Sharia, IAIN Metro, 2024)
This study critically examines the concept of nationhood and nationalism as understood by the Salafi group and analyzes the implementation of hadiths related to nationalism within the framework of contemporary Islamic law. Using a qualitative field research approach, the study focuses on approximately 200 Salafi adherents spread across Java and Sumatra. Informants were selected through purposive sampling, and data collection methods included interviews, surveys, and documentation. The research uncovers diverse interpretations of nationhood and nationalism within the Salafi community. A minority of Salafi adherents view nationalism as lacking a strong foundation in Islamic law, considering it a secular concept incompatible with Shari'ah. However, the majority, influenced by contextualist approaches in contemporary Islamic jurisprudence, argue that nationalism aligns with Islamic principles, particularly when understood as a form of maslahah and ukhuwwah wathaniyyah. This perspective is supported by contemporary Islamic scholars who emphasize protecting societal harmony and national unity as part of maqasid al-shari'ah. In practice, Salafi adherents demonstrate their acceptance of nationalism through various socio-religious activities. For instance, Salafi educational institutions integrate the study of Indonesia's independence history into their curriculum, emphasizing the moral responsibility of contributing to national welfare. This study makes academic contributions by providing a deep understanding of how contemporary Salafi groups connect Islamic teachings with modern concepts of nationhood, enriching the discourse on the adaptability of Islamic law in addressing contemporary socio-political challenges, and offering a practical framework for integrating religious values with national identity. It also contributes to discussions on pluralism and nation-building within an Islamic context.